Leukocytes: The Double-Edged Sword in Fibrosis - Jakub Kryczka; Joanna Boncela (Hindawi Limited, 2015)
Skin tissue scar formation and fibrosis are often characterized by the increased production and deposition of extracellular matrix components, accompanied by the accumulation of a vast number of myofibroblasts. Scaring is strongly associated with inflammation and wound healing to regain tissue integrity in response to skin tissue injury. However, increased and uncontrolled inflammation, repetitive injury, and individual predisposition might lead to fibrosis, a severe disorder resulting in the formation of dense and stiff tissue that loses the physical properties and physiological functions of normal tissue. Fibrosis is an extremely complicated and multistage process in which bone marrow-derived leukocytes act as both pro- and antifibrotic agents, and therefore, few, if any, effective therapies are available for the most severe and lethal forms of fibrosis. Herein, we discuss the current knowledge on the multidimensional impact of leukocytes on the induction of fibrosis, focusing on skin fibrosis.